Investigating The Effective Factors In The Internal Audit Of Organizations (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study examined the factors affecting the effectiveness of internal audit.  The effect of two intra-organizational factors of internal audit competence, the interaction of internal and external auditors as an independent variable on the effectiveness of internal audit (dependent variable) was tested.  The statistical sample is estimated at 200 managers and auditors according to Krejcie and Morgan table.  According to the statistical population, the whole population has been selected as a sample and 170 usable questionnaires were obtained from which we examined the results of the research.  The results of the present study show that the variables of audit competence within the interaction of internal and external auditors have a significant relationship with the effectiveness of internal audit.